Low serum insulin-like growth factor-I (IGF-I) level is associated with increased risk of vascular dementia. (December 2017) - Quinlan, Patrick; Horvath, Alexandra; Nordlund, Arto; Wallin, Anders; Svensson, Johan
Highlights: Prospective study in a single memory clinic (n = 342). Baseline serum IGF-I was measured in subjective or objective cognitive impairment. Mean follow-up of 3.6 years. Low serum IGF-I associated with increased risk of subsequent vascular dementia. IGF-I was not associated with the risk of all-cause dementia or Alzheimer's disease. Abstract: Background: Insulin-like growth factor-I (IGF-I) is important for the adult brain, but little is known of the role of IGF-I in Alzheimeŕs disease (AD) or vascular dementia (VaD). Methods: A prospective study of 342 patients with subjective or objective mild cognitive impairment recruited at a single memory clinic. We determined whether serum IGF-I concentrations at baseline were associated with the risk of all-cause dementia, AD, or VaD. Patients developing mixed forms of AD and VaD were defined as suffering from VaD. The statistical analyses included Cox proportional hazards regression analysis. Results: During the follow-up (mean 3.6 years), 95 (28%) of the patients developed all-cause dementia [AD, n = 37 (11%) and VaD, n = 42 (12%)]. Low as well as high serum IGF-I (quartile 1 or 4 vs. quartiles 2–3) did not associate with all-cause dementia [crude hazard ratio (HR) 1.30, 95% confidence interval (CI): 0.81–2.08 and crude HR 1.05, 95% CI: 0.63–1.75, respectively] or AD (crude HR 0.79, 95% CI: 0.35–1.79 and crude HR 0.94, 95% CI: 0.43–2.06, respectively]. In contrast, low serum IGF-I concentrations were associated with increased risk of VaD (quartile 1 vs. quartiles 2–3, crude HR 2.22, 95% CI: 1.13–4.36). The latter association remained significant also after adjustment for multiple covariates. Conclusions: In a memory clinic population, low serum IGF-I was a risk marker for subsequent VaD whereas low IGF-I did not associate with the risk of AD. High serum IGF-I was not related to the risk of conversion to dementia.